Effects of Communication Range, Noise and Help Request Signal on Particle Swarm Optimization with Area Extension (AEPSO) - Atyabi, Adham; Phon-Amnuaisuk, Somnuk; Ho, Chin Kuan (2007)
Particle Swarm Optimization (PSO) method is an Evolutionary algorithm, which outperformed other evolutionary algorithms, such as; GA. PSO method is inspired by animal's group work and social behaviors. Particle Swarm Optimization with Area Extension (AEPSO) was introduced to solve the weaknesses of Basic PSO in static, dynamic optimization tasks (i.e. a group of robots disarm a set of time bomb placed at random in environment). This paper, investigated the effectiveness of AEPSO in a Real-Time problem with a noisy environment. We also explored the effectiveness of different communication ranges and help request on AEPSO.